2020
DOI: 10.1080/15384101.2020.1743912
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Exosomes-carried microRNA-26b-5p regulates microglia M1 polarization after cerebral ischemia/reperfusion

Abstract: Exosome and microRNAs (miRs) are implicated in ischemia/reperfusion (I/R) process. In this study, I/R mouse model was established, and exosomes derived from human umbilical cord mesenchymal stem cells (hUCMSCs) were isolated, identified, and injected to I/R mice to observe nerve injury and microglia M1 polarization. The differentially expressed genes in I/R microglia from databases were analyzed, and miRs differentially expressed in exosomes-treated microglia were analyzed by microarray. miR-26b-5p expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 40 publications
2
57
0
Order By: Relevance
“…As the main immune cells resident in brain tissue, it has been proposed that microglia play an essential role in the progression of neuroinflammation (39). A recent study demonstrated that microglia acquired an M1 phenotype and secreted abundant pro-inflammatory cytokines during I/R injury (40). Immunofluorescence assay in this study showed that the microglia was activated in I/R injury induced cerebral pyroptosis.…”
Section: Discussionsupporting
confidence: 51%
“…As the main immune cells resident in brain tissue, it has been proposed that microglia play an essential role in the progression of neuroinflammation (39). A recent study demonstrated that microglia acquired an M1 phenotype and secreted abundant pro-inflammatory cytokines during I/R injury (40). Immunofluorescence assay in this study showed that the microglia was activated in I/R injury induced cerebral pyroptosis.…”
Section: Discussionsupporting
confidence: 51%
“…Exosome-shuttled miR-92b-3p from ischemic preconditioned astrocytes protects neurons against oxygen and glucose deprivation (28). Exosomal miR-26a-5p level has been identi ed to be decreased in hUCMSCs, and exosomal miR-26b-5p from hUCMSCs could repress M1 polarization of microglia by targeting CH25H to inactivate the TLR pathway, then nally relieve nerve injury after cerebral I/R (29). In this study, we found that miR-26a-5p was downregulated in MSCs-derived exosomes of MCAO and OGD model.…”
Section: Discussionmentioning
confidence: 99%
“…In an established ischemia/reperfusion (I/R) rat model, exosomal mir‐26b‐5p inhibits M1 polarization of microglia via targeting CH25H and inactivating the TLR pathway, leading to reduced nerve injury after cerebral I/R. A reduction of exosomal mir‐26b‐5p has the opposite effect 71 . Recently, it was shown that expression levels of inflammatory cytokines elevate, whereas anti‐inflammatory cytokines (IL‐4, IL‐10) and mir‐30d‐5p decrease in AIS patients compared with normal control.…”
Section: Regulation Of the Nvu By Ncrnas In Ismentioning
confidence: 99%